(untitled) - Matthews, G. A. (Hoboken, NJ, 2013)
Expanded authorship: all are well-known internationally for their work in this area Fully updated and revised edition of well-respected and widely-used book Essential reference work for all those involved in crop protection Vital information for increasing agricultural productivity to feed the ever growing population
Keywords: Pesticides,Spraying and dusting in agriculture,Spraying equipment,Thuốc trừ sâu; Application,Ứng dụng